Transitory and Permanent Features of Shocks in Renewable Energy Consumption in Africa: Evidence from Seemingly Unrelated Regression (American Journal of Energy and Natural Resources, 2024)
This research work examines the stability and stationary features of the renewable energy consumption in the selected ten (10) African countries between the period of 1991 and 2023. The study aims at finding out whether the shocks coming from the renewable energy consumption management policies would make the modern energy to revert quickly to equilibrium (transitory) or move it farther away from equilibrium (permanent). Using a more sophisticated estimation technique – Seemingly Unrelated Regression (SUR-ADF), findings from the study reveals that the renewable energy consumption in the major oil producing countries in Africa has a stationary process and therefore giving it the potential to revert back to equilibrium by itself without major policy formulation. Whereas, non-stationary features were identified for non-oil producing countries, thereby making the renewable energy consumption management policies to be effective for the countries.